The MVD 4th Division Operation in Lithuania in 1946 - Starkauskas, Juozas (Genocidas ir rezistencija, 1998)
At the beginning of 1946, both the party and the chekist leadership in Moscow and Vilnius realised that they were facing a long war of attrition with our partisans. Not only Beria’s most ambitious plan “to crush the nationalist armed underground in two or three weeks”, but also his much more realistic plans to do so in a few months, six months, a year, had failed. Something had to be done. That ‘something’ was the establishment of permanent garrisons in the centres of the districts and in many community centres of municipalities.